(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2024)
European co-productions are usually the most ambitious European films, combining multiple sources of financing and targeting both transnational audiences and critical acclaim. However, their success with audiences is often quite limited in terms of admissions. In this article, we investigate the sources of this audience challenge for European co-productions adopting the perspective centered on audience design. We look at what we define as “ideal European co-productions”—films of high artistic value with festival visibility, an “ideal script” and clear socio-cultural and political value. We identify, drawing primarily on literature in theatre studies, four different groups of target audiences for these films—average spectators, emancipated spectators, spect-actors and emancipated spect-actors—and offer a framework for understanding what mobilizes these audience groups to seek out and view films. We then use Quo Vadis, Aida?, a 2020 film by Jasmila Žbanić, as an in-depth case study to show how, in practice, a lack of strategy at both production and distribution stage can result in failing to reach the target audiences even for films that show significant audience potential and have well-defined socio-political goals. We end the study pointing to the limitations of our work as well as offering suggestions for further research and policy development.